Accelerated ferumoxytol‐enhanced 4D multiphase, steady‐state imaging with contrast enhancement (MUSIC) cardiovascular MRI: validation in pediatric congenital heart disease. (11th November 2016) - Zhou, Ziwu; Han, Fei; Rapacchi, Stanislas; Nguyen, Kim‐Lien; Brunengraber, Daniel Z.; Kim, Grace‐Hyun J.; Finn, J. Paul; Hu, Peng
Abstract: The purpose of this work was to validate a parallel imaging (PI) and compressed sensing (CS) combined reconstruction method for a recently proposed 4D non‐breath‐held, multiphase, steady‐state imaging technique (MUSIC) cardiovascular MRI in a cohort of pediatric congenital heart disease patients. We implemented a graphics processing unit accelerated CS‐PI combined reconstruction method and applied it in 13 pediatric patients who underwent cardiovascular MRI after ferumoxytol administration. Conventional breath‐held contrast‐enhanced magnetic resonance angiography (CE‐MRA) was first performed during the first pass of ferumoxytol injection, followed by the original MUSIC and the proposed CS‐PI MUSIC during the steady‐state distribution phase of ferumoxytol. Qualities of acquired images were then evaluated using a four‐point scale. Left ventricular volumes and ejection fractions calculated from the original MUSIC and the CS‐PI MUSIC were also compared with conventional multi‐slice 2D cardiac cine MRI. The proposed CS‐PI MUSIC reduced the imaging time of the MUSIC acquisition to 4.6 ± 0.4 min from 8.9 ± 1.2 min. Computationally intensive image reconstruction was completed within 5 min without interruption of sequential clinical scans. The proposed method (mean 3.3–4.0) provided image quality comparable to that of the original MUSIC (3.2–4.0) (all P  ≥ 0.42), and better than conventional breath‐held first‐pass CE‐MRA (1.1–3.3) for 13 anatomical structures (all P ≤ 0.0014) with good inter‐observer agreement ( κ  > 0.46). The calculated ventricular volumes and ejection fractions from both original MUSIC ( r  > 0.90) and CS‐PI MUSIC ( r  > 0.85) correlated well with 2D cine imaging. In conclusion, PI and CS were successfully incorporated into the 4D MUSIC acquisition to further reduce scan time by approximately 50% while maintaining highly comparable image quality in a clinically practical reconstruction time. Abstract : In this work we implemented and evaluated an accelerated image and fast reconstruction method for a recently proposed 4D multi‐phase, steady‐state imaging technique on a cohort of pediatric patients with congenital heart disease. The image reconstruction was carried out on a custom‐built parallelized image reconstruction system that imbedded in the clinical workflow without interrupting normal clinical practice. The proposed strategy halved the acquisition time of the original technique and achieved similar image quality and quantitative assessment.